2010
DOI: 10.1083/jcb.201007136
|View full text |Cite
|
Sign up to set email alerts
|

Revolving movement of a dynamic cluster of actin filaments during mitosis

Abstract: Arp2/3 actin filament nucleating complex drives circumnavigation of cortical actin clusters during mitosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(88 citation statements)
references
References 34 publications
(36 reference statements)
3
84
1
Order By: Relevance
“…The basis for these changes is not known, but we showed that inhibition of Cdk1 activity reduced cable-assembly rates and cable intensity in vivo. Recent reports in metazoans revealed up-regulation of actin assembly during metaphase (42,43,45). However, which types of actin filament networks are being regulated and which actin nucleation systems are being regulated are unclear.…”
Section: Understanding How Actin Cables Of Defined Architecture and Pmentioning
confidence: 99%
See 3 more Smart Citations
“…The basis for these changes is not known, but we showed that inhibition of Cdk1 activity reduced cable-assembly rates and cable intensity in vivo. Recent reports in metazoans revealed up-regulation of actin assembly during metaphase (42,43,45). However, which types of actin filament networks are being regulated and which actin nucleation systems are being regulated are unclear.…”
Section: Understanding How Actin Cables Of Defined Architecture and Pmentioning
confidence: 99%
“…Recently, F-actin assembly was found to be regulated by the cell cycle in vertebrates (43,45). Actin bundles assembled in metaphase were thicker and/or more prevalent than those assembled in interphase (43).…”
Section: Reconstitution Of Bni1-derived Actin Cable Assembly In Mitotmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, the spindle F‐actin has been shown to surround mitotic spindles during early Xenopus embryo mitosis 22. Arp2/3 protein complex, which is involved in the nucleation and assembly of branched actin filaments, has been shown to participate in the formation of the spindle F‐actin 52, 53. In summary, we demonstrate that ADD1 phosphorylation at S726 is important for its interaction with TPX2 and for spindle pole integrity.…”
Section: Discussionmentioning
confidence: 64%